Variation in Amygdalin Content in Kernels of Six Almond Species (Prunus spp. L.) Distributed in China - Wang, Wei; Xiao, Xun-Ze; Xu, Xin-Qiao; Li, Zhen-Jian; Zhang, Jun-Ming (Frontiers in Plant Science, 2022)
Amygdalin, a naturally occurring compound, is one of the main active ingredients of the Chinese raw bitter almond. The variation in amygdalin composition of seed kernels among the six almond species was determined, and relationships with geoenvironmental factors were analyzed. The amygdalin content exhibited great diversity, ranging from 0.0004 g/100g to 9.73 g/100g. The highest level of amygdalin was detected in Tangut almond, with 5.45-9.73 g/100g. The other kernels showed a range from 3.14 g/100g to 6.80 g/100g in wild almond and from 3.00 g/100g to 4.22 g/100g in longstalk almond. Amygdalin in common almond was almost undetectable. Factor analysis showed that amygdalin content in Prunus spp. kernels increased with altitude and decreased with the degree of aspect. Many environmental factors were closely related to amygdalin content, including annual precipitation (Bio12), UV intensity, and topsoil base saturation (T_BS), which all had a significant effect on amygdalin content. The amygdalin content is closely related to rainfall indicators, especially annual precipitation (Bio12), with the highest factor analysis value (3.63). Water regulates amygdalin in diverse ways. Because amygdalin is water-soluble, water can reduce the inhibitory effect of amygdalin on germination and regulate the synthesis of amygdalin at the late stage of germination by activating the amygdalin synthesis genes CYP79D16 and CYP71AN24. This study expanded the understanding of amygdalin in almond resources and provided direction for the regulation of amygdalin.